Dos crimes contra o sistema financeiro nacional: a responsabilidade penal dos administradores de cooperativas de crédito - Renata Rodrigues de Padua (2012)
The economic order receives the form of capitalist production and must accomplish the commitment of economic democratization. The national financial system is a functional arm of the economic order and is subordinated to the interests of the collectivity and to the balanced development of the country. The national system of cooperative credit (mostly made by credit unions) have a bank differentiated social function because it operates mostly in peripheral regions, spreading access to credit and also promoting recycling of financial resources. The economic criminality, in the current social setting, is very harmful, which was confirmed by criminological studies that originated the theory of white collar. The administrator of the credit union does not fit entirely on the concept of being a white-collar staff. Not always holds the political-economic power which characterizes these subjects. Despite the harmfulness caused by violations of legal-criminal goods on some individuals, it did not advocate for an autonomous economic criminal right. The garantism matter of the criminal right must be observed. The concept of the legal interests reveals to be indispensable to a material understanding of the unfair concept, to restrict a punitive activity and to differentiate the criminal-law function. The financial system is a legal-criminal good, in other words, is a value that meets the requirements of legitimacy (filters of moderation). As the legal interests and functions are diverse elements, it is observed that the type of auxiliary supervision and the cooperative governance system are tools to assure those already mentioned above. Many types of criminal law in 7492, 1986, does not criminalize legal rights, but duties.